Natural ventilation in greenhouse with anti-insect screens evaluated with a computational fluid model: Uso de pantallas anti-insectos en un invernadero colombiano - Villagran, Edwin Andrés (2020)
Introduction. In Colombia, horticultural production in the low tropics is limited mainly by biotic factors such as pest attacks, pathogens, and abiotic factors such as extreme values of temperature, solar radiation, wind, and precipitation. Objective. To evaluate two types of anti-insect screens in the ventilation areas of a naturally ventilated Colombian greenhouse in order to analyze the effect on the ventilation rates and the generated microclimate. Materials and methods. The study was carried out in 2019 in the department of Magdalena, Colombia. The methodological approach included the use of a 2-D computational fluid model (CFD) for the development of fifteen steady-state simulations. The CFD model was experimentally validated in the prototype of the real greenhouse evaluated. Results. Goodness-of-fit parameters between measured and simulated data showed absolute mean error (MAE) and root mean squared error (RMSE) values for temperature and relative humidity of 0.15 and 0.32 °C, 2.41 and 2.73 %, respectively. There was an average reduction in ventilation rates between 55.3 and 77.1 % compared to the reference scenario that did not include the presence of anti-insect screens, this reduction generated modifications in the behavior of the temperature and relative humidity variables inside the greenhouse, with a marked heterogeneous spatial distribution. Conclusion. The most inadequate microclimatic conditions occurred in scenarios of low external wind speed; therefore, it is recommended to select and implement some type of anti-insect screen in the ventilation areas of a greenhouse based on the local behavior of this variable.